92.5k views
0 votes
6 = 3x - 9

x + 4 < 1

x/2 + 3 = -5

1 Answer

5 votes

Answer:

see explanation

Explanation:

1

6 = 3x - 9 ( add 9 to both sides )

15 = 3x ( divide both sides by 3 )

5 = x

2

x + 4 < 1 ( subtract 4 from both sides )

x < - 3

3


(x)/(2) + 3 = - 5

Multiply terms on both sides by 2

x + 6 = - 10 ( subtract 6 from both sides )

x = - 16

User QuinnChen
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.